2016 ALGEBRAIC PROOF FERMAT'S LAST THEOREM (2-18) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In 1995, A, Wiles [2], [3], announced, using cyclic groups ( a subject area which was not available at the time of Fermat), a proof of Fermat's Last Theorem, which is stated as fol-lows: If is an odd prime and x; y; z; are relatively prime positive integers, then z 6= x + y: In this note, a new elegant proof of this result is presented. It is proved, using elementary algebra, that if is an odd prime and x; y; z; are positive integers satisfying z = x + y; then z; y; x; are each divisible by :